High-toughness ultrathin asphalt overlay and application

By using high-performance modified emulsified asphalt and ultra-high viscosity modified asphalt in ultra-thin layer cover technology, combined with asynchronous construction technology, the problems of poor interlayer bonding and high construction costs in the existing technology have been solved, and efficient, environmentally friendly and economical pavement maintenance effects have been achieved.

CN119615696AInactive Publication Date: 2025-03-14HANGZHOU ASPHALT MIXING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510162364.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ultra-thin layer cover preventive maintenance technology has problems such as poor bonding between layers, high construction costs, and high construction temperature, which is difficult to meet the requirements of road surface use.

Method used

High-performance modified emulsified asphalt is used as interlayer bonding material and ultra-high viscosity modified asphalt is used as cover material. Through mix ratio design and asynchronous construction technology, the bonding effect and construction efficiency are improved.

Benefits of technology

The excellent bonding effect of interlayer bonding materials and the good high-temperature rut resistance and water damage resistance of asphalt mixture are achieved, which reduces construction temperature, saves energy and is environmentally friendly, and reduces construction costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-toughness ultrathin asphalt overlay and application. The high-toughness ultrathin asphalt overlay comprises an interlayer binding material and an asphalt mixture, the preparation method of the interlayer binding material comprises the following steps: adding the anionic emulsifier into water, heating at 70-80 DEG C, adding the matrix asphalt and the high-viscosity modifier, and grinding by using a horizontal colloid mill to obtain high-performance modified emulsified asphalt, namely the interlayer binding material. The asphalt mixture is prepared from 5.3 to 5.9 percent of ultrahigh-viscosity modified asphalt and the balance of aggregate; the aggregate is prepared from 69.8 to 78.8 percent of coarse aggregate, 15.9 to 20.7 percent of fine aggregate and the balance of filler. According to the invention, the high-performance modified emulsified asphalt is used as an interlayer binding material, the ultrahigh-viscosity modified asphalt is used as an overlay material, the mixing proportion design is carried out on the ultra-thin ultrahigh-viscosity modified asphalt mixture, and the performance and asynchronous construction technology research is carried out, so that not only is the actual engineering value realized, but also the construction cost is reduced. And guiding significance and reference value can be generated for research and construction of preventive maintenance materials for asphalt roads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road maintenance, and in particular to a high-toughness ultra-thin asphalt overlay layer and its application. Background Art

[0002] Ultra-thin overlay is a functional overlay of asphalt pavement with a paving thickness of less than 25mm and a structural strength that meets the requirements of use. Ultra-thin overlay technology has developed into an excellent preventive maintenance method, with the advantages of fast construction speed, early opening of traffic, suitability for harsh environments, excellent anti-skid and high temperature performance, good rutting resistance and durability, etc. It can effectively repair functional damage to the road surface (pavement aging, insufficient anti-skid performance, surface detachment, potholes, rutting, subsidence and push-and-pull, etc.), thereby extending the service life of the road surface and reducing or delaying major overhauls of the road surface.

[0003] However, the current ultra-thin layer overlay preventive maintenance technology still has shortcomings, mainly including the following aspects: (1) The interlayer bonding effect of the commonly used emulsified asphalt or modified emulsified asphalt cannot meet the use requirements, so its performance needs to be further improved; (2) The use of conventional synchronous paving equipment in combination with traditional special interlayer bonding materials and high-viscosity modified asphalt mixtures for simultaneous paving is very expensive and is not conducive to promotion and application; (3) The construction temperature of the existing high-viscosity modified asphalt mixture is relatively high, which is neither energy-saving and environmentally friendly, nor economical.

[0004] In addition, compared with traditional hot-mix asphalt pavement, the thin thickness of the asphalt layer leads to higher requirements for asphalt thin layer technology in terms of materials such as asphalt and aggregate, the gradation of the thin layer asphalt mixture, and the connection between different pavement structure layers. The viscosity of the commonly used base asphalt and ordinary modified asphalt is generally low, and it is difficult to have sufficient restrictions on its skeleton, which is easy to cause the pavement to shift, loosen, peel off and other diseases, seriously affecting the durability of the ultra-thin wear layer. Summary of the invention

[0005] In view of this, the present invention proposes a high-toughness ultra-thin asphalt overlay layer and its application. The high-performance modified emulsified asphalt obtained by the present invention is used as an interlayer bonding material, and the ultra-high viscosity modified asphalt obtained is used as an overlay material. A mix ratio design is carried out for the ultra-thin layer ultra-high viscosity modified asphalt mixture, and performance and asynchronous construction technology research is carried out. It not only has practical engineering value, but also can have guiding significance and reference value for the research and construction of preventive maintenance materials for asphalt roads.

[0006] The technical solution of the present invention is achieved in this way: A high-toughness ultra-thin asphalt overlay layer, comprising an interlayer bonding material and an asphalt mixture; The preparation method of the interlayer bonding material comprises: adding an anionic emulsifier into water, heating at 70-80° C., adding base asphalt and a high-viscosity modifier, and using a horizontal colloid mill to obtain a high-performance modified emulsified asphalt, which is the interlayer bonding material; The asphalt mixture comprises: 5.3-5.9% ultra-high viscosity modified asphalt and the remainder of aggregate; the aggregate comprises 69.8-78.8% coarse aggregate, 15.9-20.7% fine aggregate and the remainder of filler; The ultra-high viscosity modified asphalt has a dynamic viscosity of 300,000-357,000 Pa•s at 60°C; The preparation method of the ultra-high viscosity modified asphalt is as follows: a stabilizer, rubber oil and SBS modifier are added to 70# base asphalt, the mixture is evenly mixed, and a compounding agent is added to obtain the ultra-high viscosity modified asphalt; The preparation steps of the asphalt mixture include: heating the ultra-high viscosity modified asphalt to 175-185°C, mixing the coarse aggregate, fine aggregate and filler, heating to 190-210°C and dry mixing for 10-20s, and then mixing the two for 40-50s to obtain an asphalt mixture at 180-195°C.

[0007] Furthermore, in the preparation method of the interlayer bonding material, the mass ratio of the base asphalt, the anionic emulsifier, the high viscosity modifier and water is 60:1-3:3-19:18-36; The solid content of the high viscosity modifier is 59%-61% and the molecular weight is 3.9×10 4 -60×10 4 ; The anionic emulsifier meets the following requirements: solid content of 45%-50%, viscosity of 10°C of 1400-1600 cps, and pH of 7.0-7.5.

[0008] Further, in the aggregate of the asphalt mixture, the coarse aggregate is 5-8 mm and 3-5 mm basalt in a mass ratio of 1:3-5 or 5-10 mm and 3-5 mm basalt in a mass ratio of 1:1-3; The fine aggregate is 0-3 mm basalt; The filler is a mineral powder obtained by grinding limestone, and the particle size specifications of the mineral powder meet the following requirements: <0.6mm, 100%; <0.15mm, 98.6%; <0.075mm, 85.3%.

[0009] Furthermore, in the preparation method of ultra-high viscosity modified asphalt, the mass ratio of the 70# base asphalt, stabilizer, rubber oil, SBS modifier and compounding agent is 100:0.5:3:7-10:1.5-3.5.

[0010] Furthermore, the stabilizer is an aromatic rubber oil, sulfur powder, a vulcanization accelerator, a vulcanization activator and a dispersing agent in a mass ratio of 30-40:30-40:20-30:1-5:1-5; the compounding agent is a styrene-butadiene-styrene block copolymer, an ethylene-vinyl acetate copolymer, an anti-stripping agent, an anti-aging agent, a dispersing agent and an aromatic rubber oil in a mass ratio of 25-35:15-20:5-10:0.5-1:2-5:20-30.

[0011] Furthermore, the gradation of the asphalt mixture satisfies the following (1) or (2): (1) The particle size specifications meet the following requirements: based on the percentage of mineral materials passing through the key sieve holes, the grading range is: 9.5 mm, 100%; 4.75 mm, 45.9%-55.6%; 2.36 mm, 22.2%-27%; 1.18 mm, 16.9%-20.4%; 0.6 mm, 13.9%-16.7%; 0.3 mm, 10.6%-12.6%; 0.15 mm, 8.4%-9.8%; 0.075 mm, 6.3%-7.3%; (2) The particle size specifications are met: based on the percentage of mineral materials passing through the key sieve holes, the grading range is: 13.2mm, 100%; 9.5mm, 99.6%-99.7%; 4.75mm, 38.9%-46.7%; 2.36mm, 25.5%-30.2%; 1.18mm, 19.5%-22.4%; 0.6mm, 16.5%-18.3%; 0.3mm, 13.3%-14.2%; 0.15mm, 11.0%-11.6%; 0.075mm, 9.6%-10.0%.

[0012] The invention discloses an application of a high-toughness ultra-thin asphalt overlay layer technology in ultra-thin overlay for road maintenance.

[0013] Furthermore, an asynchronous construction process is adopted in the ultra-thin cover.

[0014] Furthermore, the asynchronous construction process specifically includes the following steps: (1) Treat local cracks and structural defects in the underlying layer of cement concrete pavement; (2) For cement concrete slabs without many microcracks on the surface, cement concrete bridge decks with constant load requirements, cement concrete tunnels with clear height requirements, or cement concrete pavements with fixed elevations, fine milling operations are used for interface treatment; For cement concrete slabs with many micro cracks on the surface, or cement concrete bridge decks with no dead load requirements but high requirements for the structural bearing capacity of the bridge itself, shot blasting is used for interface treatment; (3) The surface of the cement concrete slab specimen is subjected to a pressure of 0.7 kg / m 2 Spray the interlayer bonding material at a temperature of 70-80°C, wait for 30-35 minutes for it to demulsify, and then spread the asphalt mixture with a thickness of 10-20mm. The paving temperature should be greater than 165°C to ensure that the wheels do not stick. (4) Rolling process, the requirements are as follows: the compaction degree of the asphalt concrete overlay surface layer must be no less than 98%, and the compaction machinery is configured as one paver and two rollers, of which one is a double-steel wheel roller with a net weight of no less than 10 tons. A small hand-held vibratory roller is also required to handle the side seam area. The rolling of the mixture is divided into three stages: initial compaction, secondary compaction and final compaction.

[0015] Furthermore, in step (4), the initial pressure is preferably at a speed of 1.5-2.0 km•h. -1 , the maximum is no more than 3km•h -1 , rolling twice, the initial rolling temperature is not less than 150℃; The suitable speed of the re-pressing is 2.5-3.5 km•h -1 , the maximum is no more than 5km•h -1 , rolling 1-2 times; The suitable speed of the final pressure is 2.5-3.5 km•h -1 , the maximum is no more than 5km•h -1 , rolling at least 2 times, and the surface temperature at the end of rolling shall not be lower than 90℃.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses high-performance modified emulsified asphalt as an interlayer bonding material and ultra-high viscosity modified asphalt as a covering material, designs a mix ratio for an ultra-thin layer of ultra-high viscosity modified asphalt mixture, and studies performance and asynchronous construction technology. This not only has practical engineering value, but also has guiding significance and reference value for the research and construction of preventive maintenance materials for asphalt roads.

[0017] 2. The high-toughness ultra-thin asphalt overlay layer of the present invention includes an interlayer bonding material and an asphalt mixture. The interlayer bonding material has an excellent bonding effect and does not stick to wheels. The asphalt mixture has good high-temperature rutting resistance and water damage resistance, and the ultra-high viscosity modified asphalt has a good bonding effect with the aggregate.

[0018] 3. The present invention uses traditional construction equipment to asynchronously construct high-performance interlayer bonding materials and ultra-high viscosity modified asphalt mixtures, and the effect can reach or approach the good road performance and durability of traditional ultra-thin overlay synchronous construction. At the same time, the construction temperature of the present invention is about 10°C lower than the temperature of conventional hot-mix mixtures, which is both energy-saving and environmentally friendly. The paving technology of the present invention takes into account economy, energy saving, environmental protection and durability, has good economic and social benefits, has guiding significance and reference value for the material design and construction of thin-layer asphalt paving technology, and also has practical engineering value. DETAILED DESCRIPTION

[0019] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0020] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0021] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0022] The anti-stripping agent of the present invention is a quaternary ammonium salt, which can be CTAB, DTAC or DDAB.

[0023] The antioxidant of the present invention is antioxidant 1010.

[0024] The dispersing aid of the present invention is furfural or polyethylene wax.

[0025] The aromatic rubber oil of the present invention is heavy aromatic oil or C9 aromatic oil.

[0026] The vulcanization accelerator of the present invention is TMTD.

[0027] The vulcanization activator of the present invention is a metal oxide activator, which may be ZnO or MgO.

[0028] Example 1 A high-toughness ultra-thin asphalt overlay layer, comprising an interlayer bonding material and an asphalt mixture; The preparation method of the interlayer bonding material comprises: adding 2% anionic emulsifier into 27% water, heating at 70-80° C., adding 60% base asphalt and 11% high viscosity modifier, and using a horizontal colloid mill to obtain high-performance modified emulsified asphalt as the interlayer bonding material; The basic properties of the high viscosity modifier are shown in Table 1; Table 1

[0029] The basic properties of anionic emulsifiers are shown in Table 2; Table 2

[0030] The performance indicators of the obtained interlayer bonding material are shown in Table 3; Table 3

[0031] The asphalt mixture comprises: 5.6% ultra-high viscosity modified asphalt and 94.4% aggregate, wherein the aggregate comprises 73% coarse aggregate (the coarse aggregate is 5-8mm and 3-5mm basalt in a mass ratio of 1:4 or 5-10mm and 3-5mm basalt in a mass ratio of 1:2), 19.7% fine aggregate (0-3mm basalt) and 7.3% filler (mineral powder obtained by grinding limestone); The particle size specifications of the mineral powder meet the requirements as shown in Table 4; Table 4

[0032] The preparation of ultra-high viscosity modified asphalt is as follows: on the basis of 70# base asphalt, 0.5% stabilizer, 3% rubber oil and 9% SBS modifier are added, mixed evenly, and 2.5% compounding agent is added to obtain the stabilizer; the stabilizer is aromatic rubber oil, sulfur powder, vulcanization accelerator, vulcanization activator and dispersing agent in a mass ratio of 35:30:20:5:5, and the compounding agent is styrene-butadiene-styrene block copolymer, ethylene-vinyl acetate copolymer, anti-stripping agent, anti-aging agent, dispersing agent and aromatic rubber oil in a mass ratio of 30:18:5:1:5:25.

[0033] The properties of the obtained ultra-high viscosity modified asphalt are shown in Table 5; Table 5

[0034] The preparation steps of the asphalt mixture include: heating the ultra-high viscosity modified asphalt to 175-185°C, mixing the coarse aggregate, fine aggregate and filler, heating them to 190-210°C and dry mixing them for 10 seconds, and then mixing the two for 40 seconds to obtain an asphalt mixture at 180-195°C; the gradation of the asphalt mixture meets (1) or (2), and the particle size specifications are shown in Table 6-7; Table 6

[0035] Table 7

[0036] Test Example 1-Asphalt mixture performance test 1. High temperature anti-rutting performance The asphalt mixture rutting test is used to evaluate the high temperature rutting resistance of the asphalt mixture. According to the asphalt mixture rutting test method in the current specification T0719, the dynamic stability of the asphalt mixture in Example 1 was measured; Conclusion: The results of the asphalt mixture rutting test show that the asphalt mixture with gradation (1) reaches 4697 times / mm, and the asphalt mixture with gradation (2) reaches 4797 times / mm, both of which meet the requirement of not less than 3000mm / time in the current specification, indicating that both gradations of asphalt mixture have good high temperature rutting resistance.

[0037] 2. Ability to resist water damage The Marshall test is used to evaluate the ability of the mixture to resist water damage. According to the Marshall stability test method for asphalt mixtures in the current specification T0709, the asphalt mixture in Example 1 is tested; Conclusion: The results of the water-immersion Marshall test show that the residual stability of the asphalt mixture with gradation (1) is 89.2%, and the residual stability of the asphalt mixture with gradation (2) is 93.8%, both of which meet the technical requirement of not less than 85% in the current specifications, indicating that they have good resistance to water damage.

[0038] 3. Freeze-thaw splitting test The freeze-thaw splitting test is to test the water stability of asphalt mixture by measuring the splitting strength ratio before and after freeze-thaw damage. According to the freeze-thaw splitting test method for asphalt mixture in the current specification T0729, the asphalt mixture in Example 1 was tested; Conclusion: The results of the freeze-thaw splitting test show that the strength ratio of the asphalt mixture after freeze-thaw to before freeze-thaw of grading (1) is 89.3%, and the strength ratio of the asphalt mixture after freeze-thaw to before freeze-thaw of grading (2) is 91.9%, both of which meet the technical requirement of not less than 80% in the specification, indicating that they have good resistance to water damage.

[0039] 4. Kentucky Fort dispersion test The Kentburgh scattering test is to evaluate whether the asphalt content in the asphalt mixture is sufficient by rotating and impacting the Marshall specimen and obtaining the information of its shedding and scattering. According to the Kentburgh scattering test method for asphalt mixture in the current specification T0733, the asphalt mixture in Example 1 was tested; Conclusion: The results of the Kentburgh scattering test show that the average value of the Kentburgh scattering test results of the asphalt mixture with gradation (1) is 2.8%, and the average value of the Kentburgh scattering test results of the asphalt mixture with gradation (2) is 4.5%, both of which meet the design requirement of no more than 8%. This shows that the asphalt in the asphalt mixture in Example 1 has a good bonding effect with the aggregate.

[0040] Comparative Example 1 The difference from Example 1 is that the interlayer bonding material is ordinary emulsified asphalt, and the rest is the same as Example 1.

[0041] That is, the preparation method of the interlayer bonding material of this comparative example includes: adding 0.8% cationic emulsifier to 39.2% water, heating at 70-80°C, adding 60% matrix asphalt, and using a horizontal colloid mill to obtain ordinary emulsified asphalt as the interlayer bonding material. The performance indicators of the cationic emulsifier are shown in Table 8; Table 8

[0042] Comparative Example 2 The difference from Example 1 is that the interlayer bonding material is SBR modified emulsified asphalt, and the rest is consistent with Example 1.

[0043] That is, the preparation method of the interlayer bonding material of this comparative example includes: adding 0.8% cationic emulsifier to 35.7% water, heating at 70-80°C, adding 60% matrix asphalt and 3.5% SBR latex modifier, heating to 140-150°C, and using a horizontal colloid mill to obtain SBR modified emulsified asphalt as the interlayer bonding material. The cationic emulsifier is the same as that of comparative example 1; the performance indicators of the SBR latex modifier are shown in Table 9; Table 9

[0044] Test Example 2-Determination of interlayer bonding effect 1. The interlayer bonding materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were set to five different spraying rates (0.3 kg / m 2 , 0.5kg / m 2 , 0.7kg / m 2 , 0.9kg / m 2 and 1.1kg / m 2 ), composite specimens were made to carry out interlaminar shear and tensile tests; Where interlaminar shear strength = interlaminar maximum shear force / (π×circular specimen diameter 2 ), interlaminar pull-out strength = interlaminar pull-out stress / (π×circular specimen diameter 2 ) The results are shown in Table 10; Table 10

[0045] From the results in Table 10, it can be seen that for the same interlayer bonding material in Example 1, Comparative Example 1 and Comparative Example 2, as the amount of interlayer bonding material sprayed increases, its shear strength shows a pattern of first increasing and then decreasing. When the spraying amount is the same, the interlayer shear strength of the high-viscosity modified emulsified asphalt in Example 1 is the largest, and the interlayer shear strength of the ordinary emulsified asphalt in Comparative Example 1 is the smallest.

[0046] For the same interlayer bonding material in Example 1, Comparative Example 1 and Comparative Example 2, as the spreading amount increases, the pull-out strength thereof shows a pattern of first increasing and then decreasing. When the spreading amount is the same, the pull-out strength of the high-performance modified emulsified asphalt in Example 1 is the largest, and the pull-out strength of the ordinary emulsified asphalt in Comparative Example 1 is the smallest.

[0047] When the spreading amount of interlayer bonding material is 0.7kg / m 2 The interlayer bonding effect is optimal.

[0048] 2. The interlayer bonding materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to durability testing. Composite specimens with a height of 10 cm and a diameter of 10 cm were subjected to different numbers of freeze-thaw cycles and then subjected to shear strength tests to evaluate the durability of the interlayer bonding effect. The results are shown in Table 11.

[0049] Table 11

[0050] As can be seen from Table 11, with the increase of the number of freeze-thaw cycles, the shear strength of the three interlayer bonding materials, the high-performance modified emulsified asphalt of Example 1, the ordinary emulsified asphalt of Comparative Example 1 and the SBR modified emulsified asphalt of Comparative Example 2, all show a gradually decreasing pattern. Among them, the interlayer shear strength decay rate of the high-performance modified emulsified asphalt of Example 1 is the slowest, and the interlayer shear strength decay rate of the ordinary emulsified asphalt of Comparative Example 1 is the fastest. When the number of freeze-thaw cycles is the same, the interlayer shear strength of the high-performance modified emulsified asphalt of Example 1 is always greater than that of the ordinary emulsified asphalt of Comparative Example 1 and the SBR modified emulsified asphalt of Comparative Example 2, and the shear strength of the ordinary emulsified asphalt of Comparative Example 1 is the smallest.

[0051] From the above, it can be seen that, compared with Comparative Examples 1 and 2, the high-performance modified emulsified asphalt of Example 1 of the present invention has the best bonding effect and the best durability.

[0052] 3. The interlayer bonding materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested for wheel sticking effect. The results showed that the high-performance modified emulsified asphalt in Example 1 of the present invention did not stick to the wheels, while Comparative Example 1 and Comparative Example 2 showed different degrees of wheel sticking.

[0053] Application example - asynchronous construction (1) Treat local cracks and structural defects in the underlying layer of cement concrete pavement; (2) For cement concrete slabs without many microcracks on the surface, cement concrete bridge decks with constant load requirements, cement concrete tunnels with clear height requirements, or cement concrete pavements with fixed elevations, fine milling operations are used for interface treatment; For cement concrete slabs with many micro cracks on the surface, or cement concrete bridge decks with no dead load requirements but high requirements for the structural bearing capacity of the bridge itself, shot blasting is used for interface treatment; (3) The surface of the cement concrete slab specimen is subjected to a pressure of 0.7 kg / m 2 Spray the interlayer bonding material at a temperature of 70-80°C, wait for 30-35 minutes for it to demulsify, and then spread the asphalt mixture to ensure that it does not stick to the wheels, with a thickness of 10-20mm; Before paving, the splicing status of the screed plate should be checked, and the main plate of the screed plate should be adjusted to eliminate the gap in the middle as much as possible to prevent the material from getting stuck and causing the middle pull marks on the paving surface. Before paving, the screed plate should be preheated to above 135℃, and the paving temperature of the mixture should be above 165℃; (4) Rolling process, the requirements are as follows: the compaction degree of the asphalt concrete overlay surface layer must be no less than 98%, and the compaction machinery is configured as one paver and two rollers, of which one double steel wheel roller with a net weight of no less than 10 tons is configured, and a small hand-held vibratory roller is also required to handle the side seam area. The rolling of the mixture is divided into three stages: initial compaction, secondary compaction and final compaction. The appropriate speed for initial compaction is 1.5-2.0 km•h -1 , the maximum is no more than 3km•h -1 , rolling twice, the initial rolling temperature is not less than 150℃; the appropriate speed for re-rolling is 2.5-3.5km•h -1 , the maximum is no more than 5km•h -1 , rolling 1-2 times; the suitable speed for final rolling is 2.5-3.5km•h -1 , the maximum is no more than 5km•h -1 , rolling at least 2 times, and the surface temperature at the end of rolling shall not be lower than 90℃.

[0054] Test Example 3 On-site road performance test and evaluation are carried out for corresponding use cases, mainly including long-term tracking observation of anti-skid performance, water-tightness and road technical conditions.

[0055] 1. Anti-slip effect The above-mentioned road section was tested by the sand spreading method and the pendulum friction coefficient tester method, and a total of 305 sets of test data of structural depth and friction coefficient were collected. The minimum test values ​​of the road surface structural depth and friction coefficient of the test section were 0.8mm and 53BPN respectively, and the cumulative proportions distributed in the 0.9-1.1mm range and the 60-80BPN range were both greater than 80%. It is shown that after the application example of the present invention is implemented, it has good anti-skid performance and can ensure the safety of the vehicle during driving.

[0056] 2. Watertight performance Using the 61 sets of water permeability coefficient sample data collected, the maximum value of the test sample of the water permeability coefficient is 60mL / min, which meets the technical requirement of less than 80mL / min, and the number of samples with a water permeability coefficient of 0mL / min is 17, accounting for 28%. This shows that the application example of the present invention has a good water sealing effect, which can effectively prevent the road surface water from infiltrating into the original road surface structure and causing early water damage. In addition, the application example of the present invention will produce a secondary compaction effect under the action of the wheel load, further ensuring the water-tight performance of the road surface.

[0057] 3. Flatness A 3m ruler and a feeler gauge were used to test the flatness of four roads, with a total of 610 points, of which 578 points had a maximum flatness gap of less than 3mm, with a pass rate of 93%. This shows that the application example of the present invention has a good flatness repair capability, and can greatly improve the flatness level of the road surface after implementation.

[0058] 4. Crack resistance tracking In order to understand the degree of attenuation of the technical condition of the road surface at the actual engineering site, a long-term road condition tracking observation was conducted on four roads, and no diseases such as displacement, potholes, and peeling were found, and the overall road condition was good. This shows that the application example of the present invention has good performance in resisting cracking and shear deformation, and no diseases such as cracking occurred.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-toughness ultra-thin asphalt overlay layer, characterized in that: Including interlayer bonding materials and asphalt mixture; The preparation method of the interlayer bonding material comprises: adding an anionic emulsifier into water, heating at 70-80° C., adding base asphalt and a high-viscosity modifier, and using a horizontal colloid mill to obtain a high-performance modified emulsified asphalt, which is the interlayer bonding material; The asphalt mixture comprises: 5.3-5.9% ultra-high viscosity modified asphalt and the remainder of aggregate; the aggregate comprises 69.8-78.8% coarse aggregate, 15.9-20.7% fine aggregate and the remainder of filler; The ultra-high viscosity modified asphalt has a dynamic viscosity of 300,000-357,000 Pa•s at 60°C; The preparation method of the ultra-high viscosity modified asphalt is as follows: a stabilizer, rubber oil and SBS modifier are added to 70# base asphalt, the mixture is evenly mixed, and a compounding agent is added to obtain the ultra-high viscosity modified asphalt; The preparation steps of the asphalt mixture include: heating the ultra-high viscosity modified asphalt to 175-185°C, mixing the coarse aggregate, fine aggregate and filler, heating to 190-210°C and dry mixing for 10-20s, and then mixing the two for 40-50s to obtain an asphalt mixture at 180-195°C.

2. A high-toughness ultra-thin asphalt overlay layer as claimed in claim 1, characterized in that: In the preparation method of the interlayer bonding material, the mass ratio of the base asphalt, the anionic emulsifier, the high viscosity modifier and water is 60:1-3:3-19:18-36; The solid content of the high viscosity modifier is 59%-61% and the molecular weight is 3.9×10 4 -60×10 4 ; The anionic emulsifier meets the following requirements: solid content of 45%-50%, viscosity of 10°C of 1400-1600 cps, and pH of 7.0-7.

5.

3. A high-toughness ultra-thin asphalt overlay as claimed in claim 1, characterized in that the asphalt In the aggregate of the mixture, the coarse aggregate is 5-8mm and 3-5mm basalt in a mass ratio of 1:3-5 or 5-10mm and 3-5mm basalt in a mass ratio of 1:1-3; The fine aggregate is 0-3 mm basalt; The filler is a mineral powder obtained by grinding limestone, and the particle size specifications of the mineral powder meet the following requirements: <0.6mm, 100%; <0.15mm, 98.6%; <0.075mm, 85.3%.

4. The high-toughness ultra-thin asphalt overlay layer as claimed in claim 1, characterized in that: In the preparation method of ultra-high viscosity modified asphalt, the mass ratio of the 70# base asphalt, stabilizer, rubber oil, SBS modifier and compounding agent is 100:0.5:3:7-10:1.5-3.

5.

5. A high-toughness ultra-thin asphalt overlay layer as claimed in claim 4, characterized in that: The stabilizer is an aromatic rubber oil, sulfur powder, a vulcanization accelerator, a vulcanization activator and a dispersing agent in a mass ratio of 30-40:30-40:20-30:1-5:1-5; the compounding agent is a styrene-butadiene-styrene block copolymer, an ethylene-vinyl acetate copolymer, an anti-stripping agent, an anti-aging agent, a dispersing agent and an aromatic rubber oil in a mass ratio of 25-35:15-20:5-10:0.5-1:2-5:20-30.

6. The high-toughness ultra-thin asphalt overlay layer as claimed in claim 1, characterized in that: The gradation of the asphalt mixture satisfies the following (1) or (2): (1) The particle size specifications meet the following requirements: based on the percentage of mineral materials passing through the key sieve holes, the grading range is: 9.5 mm, 100%; 4.75 mm, 45.9%-55.6%; 2.36 mm, 22.2%-27%; 1.18 mm, 16.9%-20.4%; 0.6 mm, 13.9%-16.7%; 0.3 mm, 10.6%-12.6%; 0.15 mm, 8.4%-9.8%; 0.075 mm, 6.3%-7.3%; (2) The particle size specifications are met: based on the percentage of mineral materials passing through the key sieve holes, the grading range is: 13.2mm, 100%; 9.5mm, 99.6%-99.7%; 4.75mm, 38.9%-46.7%; 2.36mm, 25.5%-30.2%; 1.18mm, 19.5%-22.4%; 0.6mm, 16.5%-18.3%; 0.3mm, 13.3%-14.2%; 0.15mm, 11.0%-11.6%; 0.075mm, 9.6%-10.0%.

7. Application of the high-toughness ultra-thin asphalt overlay layer described in claim 1 in ultra-thin overlay for road maintenance.

8. The use according to claim 7, characterized in that The ultra-thin cover adopts an asynchronous construction process.

9. The use according to claim 8, characterized in that The asynchronous construction process specifically comprises the following steps: (1) Treat local cracks and structural defects in the underlying layer of cement concrete pavement; (2) For cement concrete slabs without many microcracks on the surface, cement concrete bridge decks with constant load requirements, cement concrete tunnels with clear height requirements, or cement concrete pavements with fixed elevations, fine milling operations are used for interface treatment; For cement concrete slabs with many micro cracks on the surface, or cement concrete bridge decks with no dead load requirements but high requirements for the structural bearing capacity of the bridge itself, shot blasting is used for interface treatment; (3) The surface of the cement concrete slab specimen is subjected to a pressure of 0.7 kg / m 2 Spray the interlayer bonding material at a temperature of 70-80°C, wait for 30-35 minutes for it to demulsify, and then spread the asphalt mixture with a thickness of 10-20mm. The paving temperature should be greater than 165°C to ensure that the wheels do not stick. (4) Rolling process, the requirements are as follows: the compaction degree of the asphalt concrete overlay surface layer must be no less than 98%, and the compaction machinery is configured as one paver and two rollers, of which one is a double-steel wheel roller with a net weight of no less than 10 tons. A small hand-held vibratory roller is also required to handle the side seam area. The rolling of the mixture is divided into three stages: initial compaction, secondary compaction and final compaction.

10. The use according to claim 9, characterized in that In step (4), the appropriate speed of the initial pressure is 1.5-2.0 km•h -1 , the maximum is no more than 3km•h -1 , rolling twice, the initial rolling temperature is not less than 150℃; The suitable speed of the re-pressing is 2.5-3.5 km•h -1 , the maximum is no more than 5km•h -1 , rolling 1-2 times; The suitable speed of the final pressure is 2.5-3.5 km•h -1 , the maximum is no more than 5km•h -1 , rolling at least 2 times, and the surface temperature at the end of rolling shall not be lower than 90℃.

Citation Information

Patent Citations

  • Super-adhesive composite modified emulsified asphalt and preparation method thereof

    CN105482477A

  • High-viscosity and high-elasticity modified asphalt as well as preparation and application thereof

    CN107722648A

  • Construction method of interlayer high adhesion special asphalt micro-surface

    CN109054409A

  • Wheel-sticking-free emulsified asphalt of thin overlay tack coat based on asynchronous construction and preparation method of wheel-sticking-free emulsified asphalt

    CN115746335A

  • High-viscosity modified emulsified asphalt and preparation method thereof

    CN116874818A